Being Councillor and Prophet?: A Puzzle for Thomas More and Erasmus - Perona, Blandine (Erasmus studies, 2020)
By studying three letters of Erasmus to princes (to Charles, Archduke of Austria in 1516, to the same, became Charles the 5th in 1523 and to Francis the 1st in 1524), this present article intends to show that Erasmus constantly tries to resolve a puzzle which is central in Utopia's first book. Erasmus does not really choose between the answers which the fictitious More and Hythlodaeus give to the readers. He uses rhetorical accommodation as a way to be at the same time councillor and prophet, at the same time deferential and irreverent. In 1535, his last work, the Ecclesiastes, shows that during all his life he recommended the same solution. Accommodation is the way to be heard and to make words effective for princes' councillors and for preachers too.